ANALISIS BIAYA OPERASIONAL TARIF RAWAT INAP DENGAN STANDAR PELAYANAN MINIMAL (SPM) DI RUMAH SAKIT UMUM MUHAMMADIYAH METRO - Juriyana Susanti; Suyanto Suyanto; Ardiansyah Japlani (Universitas Muhammadiyah Metro, 2023)
This study aims to determine the operational costs of inpatient rates with minimum service standards at the Muhammadiyah Metro General Hospital. Data obtained from the results of interviews, observations, and documentation. Analysis of the research data was carried out using inductive qualitative data analysis. The results of the study show that the services of the Metro City Muhammadiyah Hospital are in accordance with the Minimum Service Standards made by the hospital. By grouping costs, it can be seen that the average cost per patient in class I inpatient room at Muhammadiyah Metro City Hospital is Rp. 158,403.31.